Understanding Islam at European museums / Magnus Berg, Klas Grinell. - Berg, Magnus, 1955-; Grinell, Klas (Cambridge elements. Elements in critical heritage studies, 2021)
Exhibitions of Islamic artefacts in European museums have since 1989 been surrounded by a growing rhetoric of cultural tolerance, in response to the dissemination of images of Islam as misogynist, homophobic and violent. This has produced a new public context for exhibitions of Islam and has led to major recent investments in new galleries for Islamic artefacts, often with financial support from the Gulf and Saudi Arabia. This Element addresses contemporary framings of Islam in European museums, focusing on how museums in Germany and the UK with collections of Islamic heritage realise the ICOM (International Council of Museums) definition of museums as institutions in the service of society. The authors find that far too often the knowledge of Islamic cultural heritage is disconnected from contemporary developments in museum transformations, as well as from the geopolitical contexts they are a response to.